1999
DOI: 10.1046/j.1365-2133.1999.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive angioendotheliomatosis or intravascular histiocytosis? An immunohistochemical and ultrastructural study in two cases of intravascular histiocytic cell proliferation

Abstract: Two elderly women with complex medical histories presented with erythematous patches, in one case involving the face and forearms, and in the other both elbows. Punch biopsies from both patients revealed intravascular proliferations of medium-sized and large cells with luminal occlusion typical of angioendotheliomatosis. Immunostaining did not show either lymphocytic or endothelial cell antigens but was consistent with a histiocytic differentiation of the intravascular cells in both cases, and was further subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 20 publications
7
81
0
5
Order By: Relevance
“…This rare disorder was firstly described by O'Grady et al in 1994 [9]. However, these reported cases have used different terms, involving intravascular histiocytosis, cutaneous histiocytic lymphangitis and intravascular or intralymphatic histiocytosis [2,3,8,10]. Also similar skin lesions were named angioendotheliomatosis with rheumatoid arthritis [4].…”
Section: A C D B Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rare disorder was firstly described by O'Grady et al in 1994 [9]. However, these reported cases have used different terms, involving intravascular histiocytosis, cutaneous histiocytic lymphangitis and intravascular or intralymphatic histiocytosis [2,3,8,10]. Also similar skin lesions were named angioendotheliomatosis with rheumatoid arthritis [4].…”
Section: A C D B Discussionmentioning
confidence: 99%
“…Also similar skin lesions were named angioendotheliomatosis with rheumatoid arthritis [4]. Furthermore, Rieger et al suggested that intravascular histiocytosis might be the early stage of reactive angioendotheliomatosis [10]. Rare cases of intravascular histiocytosis presenting with a clinical and histologic picture similar to that of reactive angioendotheliomatosis but showing intravascular cells with a histiocytic immunophenotype have been described [3,11].…”
Section: A C D B Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rieger et al [7] spekulieren, dass verschiedene entzünd-liche Stimuli, z. B. Kryoproteine, zu einer thrombotischen Okklusion kleiner Gefäße führen, was wiederum eine Adhä-sion mononukleärer Zellen bewirkt und durch Expression "histiozytärer" Marker (CD68+, CD163+ Mac387+, CD1A−, S100−) zu reaktiven Veränderungen an der Basallamina mit Formation endothe- Es wird diskutiert, dass die intralymphatische Histiozytose eine Stenose oder Okklusion der lymphatischen Abflusswege mit konsekutivem Stauungsödem induzieren kann, klinisch der teigig-derben Schwellung entsprechend.…”
Section: äTiologieunclassified
“…Ätiologisch werden die intralymphatischen histiozytären Aggregate entweder als Resultat einer "zellulären Drainage" des entzündlichen Prozesses der Synovia über die Lymphbahnen interpretiert [3] oder im Rahmen der vaskulären Histiozytose als frühe Form einer reaktiven Angioendotheliomatose [7].…”
Section: Rheumatoide Arthritisunclassified